2015
DOI: 10.1002/marc.201500115
|View full text |Cite
|
Sign up to set email alerts
|

Selective and Quantitative Oxidation of Xanthate End-Groups of RAFT Poly(n-butyl acrylate) Latexes by Ozonolysis

Abstract: Although various successful strategies have been reported in the past for the postpolymerization modification of the reversible addition‐fragmentation chain transfer (RAFT) terminal group in homogeneous media, no solution is proposed for the tedious case of aqueous polymer dispersions where most of the thiocarbonylthio terminal group is buried into the core of the polymer particle. In this work, ozone is proposed to tackle this important academic and industrial challenge. After preliminary model ozonolysis rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 42 publications
0
13
0
Order By: Relevance
“…In 2015, Destarac and co-workers demonstrated that xanthate groups could be efficiently cleaved from aqueous poly(n-butyl acrylate) latexes using ozone at ambient temperature. 58…”
Section: Polymer Chemistrymentioning
confidence: 99%
“…In 2015, Destarac and co-workers demonstrated that xanthate groups could be efficiently cleaved from aqueous poly(n-butyl acrylate) latexes using ozone at ambient temperature. 58…”
Section: Polymer Chemistrymentioning
confidence: 99%
“… 45 , 46 Moreover, such CTAs are colored, malodorous, and potentially toxic, so their quantitative removal is often desired for potential applications. 47 , 48 Fortunately, RAFT chain-ends can be readily cleaved using reagents such as amines, 49 ozone, 47 H 2 O 2 , 50 or excess radical initiator. 51 …”
Section: Introductionmentioning
confidence: 99%
“…Matioszek and co-workers used ozonolysis to remove xanthatebased RAFT end-groups buried within the cores of relatively low molecular weight poly(n-butyl acrylate) latex particles in aqueous media. 86 Complete removal of these RAFT end-groups was observed by UV GPC analysis within 1 h at room temperature. Colloidal stability was maintained provided that the Mn of the latex was above 5 000 g mol -1 .…”
Section: Raft End-group Removal From Pnmep-plma Diblock Copolymer Nano-objects Using Visible Light Irradiationmentioning
confidence: 99%
“…[73][74][75][76] Moreover, the vast majority of work in this area has focused on the modification of soluble chains, [77][78][79][80][81][82][83][84][85] with only a few studies examining RAFT end-group removal from block copolymer nano-objects. 86,87 Mattson and co-workers used UV light (λ = 380nm) to remove terminal trithiocarbonate end-groups with a photoredox Intensity / a.u. Please do not adjust margins Please do not adjust margins catalyst in solution (acetonitrile or N,N-dimethylacetamide).…”
Section: Raft End-group Removal From Pnmep-plma Diblock Copolymer Nano-objects Using Visible Light Irradiationmentioning
confidence: 99%